ON FERMION MASSES and MIXING IN A MODEL WITH A(4) SYMMETRY - Machado, A. C. B. [UNESP]; Montero, J. C. [UNESP]; Pleitez, V. [UNESP] (World Scientific Publ Co Pte Ltd, 2012)
In a recently proposed multi-Higgs extension of the standard model in which discrete symmetries, A(4) and Z(3) are imposed we show that, after accommodating the fermion masses and the mixing matrices in the charged currents, the mixing matrices in the neutral currents induced by neutral scalars are numerically obtained. However, the flavor changing neutral currents are under control mainly by mixing and/or mass suppressions in the neutral scalar sector.
Keywords: Discrete symmetries; fermion masses; flavor changing